Examination of Current Treatments and Symptom Management Strategies Used by Patients With Mal De Debarquement Syndrome - Canceri, Josephine M.; Brown, Rachael; Watson, Shaun R.; Browne, Cherylea J. (Frontiers in Neurology, 2018)
Introduction: Mal de Debarquement Syndrome (MdDS) is a neurological disorder which affects the vestibular system pathways, manifesting as a constant sensation of movement in the form of rocking, bobbing or swaying. The mechanism of MdDS is poorly understood and there is a lack of awareness amongst medical professionals about the condition. This study aimed to examine treatments and symptom management strategies used by MdDS patients and evaluate their self-reported effectiveness. Method: Motion-Triggered and Spontaneous/Other onset MdDS patients responded to a set of comprehensive questions as a retrospective survey regarding epidemiological details, diagnostic procedures, onset and symptom triggers, hormonal influences as well as treatments and symptom management strategies used to reduce symptoms. The Motion-Triggered questionnaire was made available through Survey Monkey and the Spontaneous/Other Onset questionnaire through Qualtrics. The link for each questionnaire was made available on online MdDS support groups and on various research websites. Descriptive statistics were used for epidemiological data and Pearson’s Chi Square tests were used for comparisons between and within both subtype groups. Results: A total of 370 patients participated in the surveys, with 287 valid responses collected for the section regarding treatment and symptom management strategies. The success of the treatments and symptom management strategies did not vary between subtypes Benzodiazepines / Antidepressants were reported as being most beneficial in reducing symptoms in both groups. Conclusion: This was the first attempt to evaluate the reported success of treatments and symptom management strategies in MdDS patients by assessing the patients’ perceived helpfulness. The treatments and symptom management strategies reported to be the most helpful in managing and/or reducing symptoms are proposed to be effective due to their stress-reducing capacities. We hope this study will broaden MdDS awareness and that this study will increase patient knowledge regarding treatments and symptom management strategies that other patients found helpful.